Familial Glucocorticoid Deficiency: the changing landscape of an eponymous syndrome - Maharaj, Avinaash V. (Frontiers in Endocrinology, 2023)
Familial Glucocorticoid Deficiency encompasses a broad spectrum of monogenic recessive disorders that theoretically solely abrogate cortisol biosynthesis. In reality, delineating clear genotype-phenotype correlations in this disorder is made complicated by marked phenotypic heterogeneity even within kindreds harbouring identical variants. Phenotypes range from isolated glucocorticoid insufficiency to cortisol deficiency plus a variety of superimposed features including salt-wasting and hypoaldosteronism, primary hypothyroidism, hypogonadism and growth defects. Furthermore, mutation type, domain topology and perceived enzyme activity do not always predict disease severity. Given the high burden of disease and implications of a positive diagnosis, genetic testing is crucial in the management of patients warranting detailed delineation of genomic variants including viable functional studies.